Farmyard hullabaloo - Andreae, Giles, 1966-; Wojtowycz, David (London : Orchard, 2000)
A collection of verses that introduce such farm animals as chickens, cows, pigs, and sheep.
2.7
K-3
Keywords: Children's poetry, English; Domestic animals -- Juvenile poetry; Domestic animals -- Poetry; English poetry